2015
DOI: 10.1016/j.cmet.2015.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Lipoxin A4 Attenuates Obesity-Induced Adipose Inflammation and Associated Liver and Kidney Disease

Abstract: SUMMARY The role of inflammation in obesity-related pathologies is well established. We investigated the therapeutic potential of LipoxinA4 (LXA4:5(S),6(R),15(S)-trihydroxy-7E,9E,11Z,13E,-eicosatetraenoic acid) and a synthetic 15(R)-Benzo-LXA4-analogue, as interventions in a 3-month high-fat-diet [HFD; 60%fat]-induced obesity model. Obesity caused distinct pathologies, including impaired glucose-tolerance, adipose inflammation, fatty liver and chronic-kidney-disease (CKD). Lipoxins (LXs) attenuated obesity- in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
166
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 188 publications
(175 citation statements)
references
References 62 publications
7
166
1
1
Order By: Relevance
“…1a), in accordance with our previous studies [29]. However, HFD-fed Adipoq −/− mice presented with an increased number of F4/80 + macrophages (p < 0.05; Fig.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…1a), in accordance with our previous studies [29]. However, HFD-fed Adipoq −/− mice presented with an increased number of F4/80 + macrophages (p < 0.05; Fig.…”
Section: Resultssupporting
confidence: 92%
“…AICAR reduced adipose inflammation in tissue explants obtained from obese human patients WAT inflammation is a key driver of obesity-related pathophysiology [26][27][28][29]. As a proof-of-principle for translating our rodent data to human pathophysiology, we investigated whether AICAR could reduce inflammation and manipulate leucocyte phenotypes in omental WAT explants taken from obese patients undergoing gastric bypass surgery.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment with LXA 4 of adipose tissue explants from aging mice-a model of adipose inflammation-leads to a decrease in IL-6 and restoration of GLUT4 and insulin receptor substrate (IRS)1 expression, indicating less inflammation and improved insulin sensitivity (21). In addition, it has recently been reported that treatment of mice with LXA 4 protects against high-fat diet (HFD)-induced adipose inflammation and hepatic lipid deposition without affecting glucose tolerance (22).…”
mentioning
confidence: 99%
“…Na verdade, a obesidade e a inflamação estão associadas e apresentam contribuição cíclica no agravamento de ambas. Corroborando diversos autores (133,134,136), nós encontramos aumentado número de macrófagos de perfil M1 nos camundongos obesos e este aumento foi ainda mais expressivo quando avaliamos os camundongos MyD88 KO obesos.…”
Section: Discussionunclassified